Aversion to Health Inequality - Pure, Income-Related and Income-Caused - Matthew Robson; Owen O'Donnell; Tom Van Ourti (Tinbergen Institute, 2023)
We design a novel experiment to identify aversion to pure (univariate) health inequality separately from aversion to income-related and income-caused health inequality. Participants allocate resources to determine health of individuals. Identification comes from random variation in resource productivity and in information on income and its causal effect. We gather data (26,286 observations) from a UK representative sample (n=337) and estimate pooled and participant-specific social preferences while accounting for noise. The median person has strong aversion to pure health inequality, challenging the health maximisation objective of economic evaluation. Aversion to health inequality is even stronger when it is related to income. However, the median person prioritises health of poorer individuals less than is assumed in the standard measure of income-related health inequality. On average, aversion to that inequality does not become stronger when low income is known to cause ill-health. There is substantial heterogeneity in all three types of inequality aversion
Keywords: C90; D30; D63; I14; 330; Inequality Aversion; Social Preferences; Health; Income; Experiment